The JFK conspiracy : the secret plot to kill Kennedy-and why it failed - Meltzer, Brad; Mensch, Josh (Flatiron Books, 2025)
"Kennedy, the thirty-fifth president of the United States, is often ranked among Americans' most well-liked presidents. Yet what most Americans don't know is that JFK's historic presidency almost ended before it began-at the hands of a disgruntled sociopathic loner armed with dynamite. On December 11, 1960, shortly after Kennedy's election and before his inauguration, a retired postal worker named Richard Pavlick waited in his car-a parked Buick-on a quiet street in Palm Beach, Florida. Pavlick knew the president-elect's schedule. He knew when Kennedy would leave his house. He knew where Kennedy was going. From there, Pavlick had a simple plan-one that could've changed the course of history. Written in the gripping, page-turning style that is the hallmark of Brad Meltzer and Josh Mensch's bestselling series, this is a slice of history vividly brought to life. Meltzer and Mensch are at the top of their game with this brilliant exploration of what could've been for one of the most compelling leaders of the 20th century"--